Isoflurane treatment for refractory and super-refractory status epilepticus in dogs - Sarpekidou, Eirini; Polyzois, Georgios; Papageorgiou, Virginia; Savvas, Ioannis; Polizopoulou, Zoe; Kazakos, George (Frontiers in Veterinary Science, 2024)
Introduction: Resistant epileptic episodes such as Refractory Status Epilepticus (RSE) and Super Refractory Status Epilepticus (SRSE) are neurological emergencies which require immediate medical treatment. Although inhalational anesthetics like isoflurane (ISO) have been proposed as a mean of seizure control in dogs, there is currently a lack of both experimental and clinical studies on this subject. Study design: Retrospective clinical study. Methods: Records of dogs that received ISO for the management of RSE and SRSE during their Intensive Care Unit (ICU) hospitalization at the Companion Animal Clinic of Aristotle University of Thessaloniki were included in the present study. The study period spanned from February 2013 to March 2023. Dogs were identified as Responders (R) when RSE/SRSE ceased after ISO administration and the dogs were successfully discharged from the ICU after ISO discontinuation, and Non Responders (NR) when RSE/SRSE ceased after ISO administration, but RSE/SRSE reoccurred after ISO discontinuation. Additional data about number and time of ISO cycles, time of ICU hospitalization, side effects of ISO administration, additional administration of Antiepileptic Drugs (AEDs) and anesthetic drugs were also recorded. Results: A total of 20 dogs with 26 recorded RSE/SRSE episodes and 26 anesthetic cycles with ISO were included in the present study. Clinical termination of seizure activity could be achieved in all episodes 100% (26/26). In 73.1%% (19/26) of the episodes ISO administration resulted in successful RSE/SRSE treatment. Poor outcome was recorded in 26.9% (7/26) of the episodes because RSE/SRSE reoccurred after ISO discontinuation, and the dogs were euthanatized or died due to cardiac arrest. Inspiratory ISO ranged between 0.5-4.0%. Median time of the anesthetic cycles with ISO was 12.67 hours (4.00-62.00). Median duration of ICU hospitalization was 48.00 hours (24.00-120.00). At least one ISO related side effect was recorded in 23/26 (88.5%) episodes. Conclusions: To the authors’ knowledge this is the first clinical study that addresses the administration of ISO for RSE/SRSE treatment in dogs. The use of ISO may be beneficial in terminating RSE/SRSE; however further prospective studies are necessary to confirm this observation.